Investigating Repair Strategies in a University EFL Context: a Conversation Analysis Approach - Shatha Alzahrani; Mona Sabir (Journal of ELT, Linguistics, and Literature, 2026)
Effective classroom interaction in EFL contexts depends on participants' ability to manage communication breakdowns through repair strategies. Despite growing interest in Conversation Analysis (CA) as a framework for examining classroom talk, its application to first-year EFL settings within Saudi higher education remains limited. This study investigates the distribution and functional use of repair strategies in EFL classrooms at King Abdulaziz University (KAU). Data were generated through systematic classroom observation across five sessions, totaling fifteen hours of instructional time, and analyzed using a CA-informed coding framework. Findings reveal that Self-Initiated Self-Repair (SISR) was the most prevalent repair type, accounting for 49% of all instances, with instructors producing twice as many SISR cases as students, a pattern indicative of a high degree of linguistic self-monitoring. While students predominantly employed lexical searching and replacement strategies, teachers drew on a broader sub-strategy repertoire to sustain interactional continuity. These patterns suggest that the KAU first academic year context supports learner autonomy in managing linguistic trouble sources, though asymmetries between teacher and student repair behavior warrant further attention. Findings carry implications for how instructional interactional space is allocated in EFL classrooms.